Restriction endonuclease cleavage map and location of unique features of the DNA of hepatitis B virus, subtype adw2. - Siddiqui, A (1979)
DNA of hepatitis B virus (HBV) of hepatitis B surface antigen (HBsAg) subtype adw2 made fully double stranded by the virion DNA polymerase and radiolabeled either by the virion DNA polymerase reaction or by nick-translation with 32P-labeled deoxynucleoside triphosphates was used to establish a map of restriction endonuclease cleavage sites by the method double and triple enzyme digestion and to determine the relative positions of several unique physical features of this DNA. The five restriction sites for enzyme HincII, the two sites each for BamHI, Ava I, and Bgl II, and the single sites for EcoRI, Pst I, Hpa I, and Taq I were positioned relative to each other. Within this map, the single-stranded region in HBV DNA has been localized and the locations of nicks in each strand (a and b) have been determined with respect to restriction sites on the circular map. Comparison of restriction endonuclease cleavage patterns of DNAs of HBV of HBsAg subtypes adw2, ayw3, and adrq+ revealed consistent differences among subtypes and occasional differences within subtypes.